2022
DOI: 10.3390/cancers14123015
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Vulnerability to ATR Inhibition in Concurrent NF1 and ATRX-Deficient/ALT-Positive High-Grade Solid Tumors

Abstract: Subsets of Neurofibromatosis Type 1 (NF1)-associated solid tumors have been shown to display high frequencies of ATRX mutations and the presence of alternative lengthening of telomeres (ALT). We studied the phenotype of combined NF1 and ATRX deficiency in malignant solid tumors. Cell lines derived from NF1-deficient sporadic glioblastomas (U251, SF188), an NF1-associated ATRX mutant glioblastoma cell line (JHH-NF1-GBM1), an NF1-derived sarcoma cell line (JHH-CRC65), and two NF1-deficient MPNST cell lines (ST88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The abovementioned connections between HR and ATRX deficiency are also intriguing from a therapeutic point of view. Recent preclinical data revealed an increased DNA-damage response and HR repair deficiency (HRD) in ATRX-deficient tumors, resulting in higher sensitivity to poly (ADP-ribose) polymerase (PARP) 42 , 43 as well as ataxia telangiectasia and Rad3-related (ATR) inhibitors 43 , 44 . PARP inhibitors are emerging new therapeutic options in the treatment of primary and recurrent GB 45 , but further clinical evidence is necessary regarding their utility.…”
Section: Discussionmentioning
confidence: 99%
“…The abovementioned connections between HR and ATRX deficiency are also intriguing from a therapeutic point of view. Recent preclinical data revealed an increased DNA-damage response and HR repair deficiency (HRD) in ATRX-deficient tumors, resulting in higher sensitivity to poly (ADP-ribose) polymerase (PARP) 42 , 43 as well as ataxia telangiectasia and Rad3-related (ATR) inhibitors 43 , 44 . PARP inhibitors are emerging new therapeutic options in the treatment of primary and recurrent GB 45 , but further clinical evidence is necessary regarding their utility.…”
Section: Discussionmentioning
confidence: 99%
“…Less common genetic drivers of NF1-associated high-grade gliomas included TP53 mutation (3/17, 18%), PIK3CA or PIK3R1 mutation (4/17, 24%), PTEN mutation (1/17, 6%), PDGFRA amplification (1/17, 6%), MYCN amplification (1/17, 6%), PPM1D mutation (1/17, 6%), and SETD2 mutation (1/17, 6%). Together, these cooperating genetic alterations may represent additional therapeutic targets beyond MEK inhibition for NF1-associated high-grade gliomas, specifically using small molecule inhibitors of CDK4/6 ( e.g., abemaciclib) and either PARP ( e.g., olaparib) or ATR ( e.g., berzosertib) given the known synthetic lethality in tumors that utilize alternative lengthening of telomeres [ 8 , 10 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that increased RS confers sensitivity to ATRis. Several genetic mutations cause alterations in RS elevation that also lead to sensitivity to ATRis, such as BRG1 loss ( SMARCA4 -deficient) [ 96 ], reduced APOBEC3B [ 137 ], MYCN amplification [ 123 ], and so on.…”
Section: Molecular Markers and Determinants Of Atri Sensitivitymentioning
confidence: 99%